التصوف بين التوظيف السياسي والثابت التاريخي (Sufism between the Political Utilization and the Historical Facts) - Ladjal, Tarek; Berahim@Ibrahim, Ahmad Zaki (Journal of Al-Tamaddun, 2012)
This paper discusses the relationship between Sufism and politics. The significance of this relationship presents itself at the heart of an emerging Western interest in Sufi political development. Western institutions have identified Tasawwuf as an internal mechanism imbedded in the Islamic system as viable option for shaping cooperation and understanding. Such an identification stems from factual ground realities embodied in certain Sufi schools, and a number of historical events, where Sufi are portrayed as foes of religion. This paper also examines the similarities and differences between classical and contemporary Sufi practices.